Structural barriers to the formation of theories about the mind: A proposal for a model-based paradigm for psychology - Daniel Kerschke (Methods in Psychology)
Psychology wields advanced empirical tools yet still resembles Kuhn's pre-paradigmatic science. I argue that progress is blocked by two ontological obstacles: the crud factor, in which variables are cross-linked, and the intrinsic opacity of subjective experience. Variable-isolation experiments or law-seeking programs struggle in such terrain. I propose a holistic gears-based framework that articulates mid-range, interrelated qualitative mechanisms and effectively orients subsequent empirical investigation. The approach decomposes contested constructs into empirically anchored parts, traces their context-bound interactions, and invites indirect tests through carefully chosen proxies. Finally, I examine institutional incentives that currently sideline heavy theoretical work and thereby sustain persistent fragmentation.